Flexible Polypropylene-Supported ZIF‑8 Membranes for Highly Efficient Propene/Propane Separation - Zhao, Yali; Wei, Yanying; Lyu, Luxi; Hou, Qianqian; Caro, Jürgen; Wang, Haihui (Journal of the American Chemical Society, 2020)
Metal–organic framework (MOF) membranes have enormous potential in separation applications. There are several MOF membranes grown on polymer substrates aimed for scale-up, but their brittleness hampers any industrial application. Herein, intergrown continuous polypropylene (PP)-supported ZIF-8 membranes have been successfully synthesized via fast current-driven synthesis (FCDS) within 1 h. The PP-supported ZIF-8 membranes exhibit a promising separation factor of 122 ± 13 for binary C3H6–C3H8 mixtures combined with excellent flexibility behavior. The C3H6/C3H8 separation performance of the PP-supported ZIF-8 membrane was found to be constant after bending the supported ZIF-8 film with a curvature of 92 m–1. This outstanding mechanical property is crucial for practical applications. Moreover, we further synthesized ZIF-8 membranes on various polymer substrates and even polymer hollow fibers to demonstrate the production scalability.